BRANCHED1: A Key Hub of Shoot Branching - Wang, Ming; Le Moigne, Marie-Anne; Bertheloot, Jessica; Crespel, Laurent; Perez-Garcia, Maria-Dolores; Ogé, Laurent; Demotes-Mainard, Sabine; Hamama, Latifa; Davière, Jean-Michel; Sakr, Soulaiman (Frontiers in Plant Science, 2019)
Shoot branching is a key process for plant growth and fitness. Newly produced axes result from axillary bud outgrowth, which is at least partly mediated through the regulation of BRANCHED1 gene expression (BRC1/TB1/FC1). BRC1 encodes a pivotal bud-outgrowth-inhibiting transcription factor belonging to the TCP family. As the regulation of BRC1 expression is a hub for many shoot-branching-related mechanisms, it is influenced by endogenous (phytohormones and nutrients) and exogenous (light) inputs, which involve so-far only partly identified molecular networks. This review highlights the central role of BRC1 in shoot branching and its responsiveness to different stimuli, and emphasizes the different knowledge gaps that should be addressed in the near future.